Vessel Health and Preservation: The Right Approach for Vascular Access - Moureau, Nancy L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This Open access book offers updated and revised information on vessel health and preservation (VHP), a model concept first published in poster form in 2008 and in JVA in 2012, which has received a great deal of attention, especially in the US, UK and Australia. The book presents a model and a new way of thinking applied to vascular access and administration of intravenous treatment, and shows how establishing and maintaining a route of access to the bloodstream is essential for patients in acute care today. Until now, little thought has been given to an intentional process to guide selection, insertion and management of vascular access devices (VADs) and by default actions are based on crisis management when a quickly selected VAD fails. The book details how VHP establishes a framework or pathway model for each step of the patient experience, intentionally guiding, improving and eliminating risk when possible. The evidence points to the fact that reducing fragmentation, establishing a pathway, and teaching the process to all stakeholders reduces complications with intravenous therapy, improves efficiency and diminishes cost. As such this book appeals to bedside nurses, physicians and other health professionals.
Preface. About the concept of VHP, beginnings, process and ideal -- Section 1. Right Assessment and Right Vein -- Chapter 1. Catheter and vein selection with avoidance of joints and danger zones -- Chapter 2. Ultrasonic assessment and placement of right device -- Section 2. Right Training -- Chapter 3. Training process, competencies, preparation for PIV, PICC, CVC insertions -- Section 3. Right Insertion -- Chapter 4. Catheter size, type, number of lumen for patient and treatment -- Chapter 5. Placement with no more than 2 attempts -- Chapter 6. Infection Prevention principles with Kits for insertion and compliance with sterile procedure (bundles, checklist, CHG, etc) -- Chapter 7. Tip positioning -- Chapter 8. Securement -- Section 4. Pediatric Vessel Health -- Chapter 9. Differences between paediatrics and adults for vein assessment -- Chapter 10. Right Site selection -- Chapter 11. Right Device assessment (type, size, no. of lumens) -- Chapter 12. Right Technology assessment -- Chapter 13. Why is VHP important in paediatrics? -- Chapter 14. Troubleshooting in paediatrics -- Section 5. Right Supplies and Technology -- Chapter 15. Ultrasound -- Chapter 16. Insertion kits for USGPIV, PICC, Midline, CVC -- Chapter 17. Antimicrobial dressings -- Chapter 18. Needleless connector issues -- Section 6. Right Care and Assessment -- Chapter 19. Daily or twice daily assessment for catheter function, dressing adherence and necessity of device -- Chapter 20. Hub disinfection issues and compliance measures -- Chapter 21. Flushing with proper techniques -- Section 7. Right Evaluation -- Chapter 22. How to evaluate a VHP program initiative -- Chapter 23. Staff education and satisfaction -- Chapter 24. Patient satisfaction -- Chapter 25. Pathway effectiveness and outcome measures.
Keywords: Nursing; Critical care medicine; Pediatrics; Nursing; Intensive Care Medicine; Pediatrics